(untitled) (Research, Society and Development, 2022)
According to the World Health Organization (WHO), almost 1 billion people lived with a mental disorder in 2019. In this context, despite the growth in the use of smartphones and the consequent increase in the offer of applications offering support and guidance services regarding health mental, E-Mental Health, studies focused on the effectiveness of these software are scarce. Therefore, this integrative review sought to identify the benefits and limitations regarding the use of software applied to mental health. For this exploratory integrative bibliographical review, articles were searched in the National Library of Medicine (PUBMED) and SciELO (Scientific Electronic Library Online) databases, using the Health Science descriptors - (DeSC) and indexers - Medical Subject Headings - ( MeSH) considering the keywords: mental health; programs, and their respective terms in English: “Mental Health”; “Software”, with the Boolean operators: “AND” and “OR”. What was concluded is that, despite the large number of E-Mental Health, although an expansion of software aimed at mental health has been observed, there is not a significant number of researches and, consequently, evidence, regarding the effectiveness of these programs.